2022
DOI: 10.1002/sstr.202200021
|View full text |Cite
|
Sign up to set email alerts
|

New Advances in Nanomaterial‐Based Antiviral Strategies

Abstract: The ongoing coronavirus disease 2019 (COVID-19) pandemic and other major viral infectious diseases have become a significant threat to people's life and economic/social development. In recent years, with the development of nanotechnology, nanomaterial-based antiviral agents have been extensively studied. However, the clinical applications of antiviral nanomaterials are still limited. Herein, the recent advances in nanomaterial-based antiviral strategies, mainly including antiviral nanodrugs, drug nanocarriers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 153 publications
0
5
0
Order By: Relevance
“…In the history of human survival and development, epidemics caused by pathogens such as viruses and bacteria have always posed a severe threat to human health. [1][2][3][4] Therefore, the development of efficient antibacterial materials is imminent. In addition, due to the overuse of antibiotics, especially against Gram-negative bacteria like Escherichia coli (E. coli) and Grampositive bacteria like Staphylococcus aureus (S. aureus), bacterial resistance to currently available bacteriostatic agents is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…In the history of human survival and development, epidemics caused by pathogens such as viruses and bacteria have always posed a severe threat to human health. [1][2][3][4] Therefore, the development of efficient antibacterial materials is imminent. In addition, due to the overuse of antibiotics, especially against Gram-negative bacteria like Escherichia coli (E. coli) and Grampositive bacteria like Staphylococcus aureus (S. aureus), bacterial resistance to currently available bacteriostatic agents is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Infecting cells is necessary for a virus in order for it to replicate itself. Therefore, inhibiting the contact between the virus and the host cell is an efficient strategy for preventing recurrent infection (Xu et al, 2022). Some research indicated that CBNPs could effectively capture and interact with viruses.…”
Section: Antiviral Mechanisms Of Cbnpsmentioning
confidence: 99%
“…Studies have revealed that some metallic and carbon-based nanomaterials like silver nanoparticles, graphene oxide, and carbon dots exhibit broad-spectrum antiviral properties. 11–17 Among them, graphene quantum dots (GQDs) as a kind of carbon dot (CD) have emerged as very potent antiviral nano-agents due to their low toxicity, extensive precursor sources, low cost, simple synthesis and ease of industrialization. 18–22 Basically, GQDs are ultra-small pieces of graphene consisting of one or a few layers (no more than 10) of graphene, and they share many properties with carbon quantum dots and graphene.…”
Section: Introductionmentioning
confidence: 99%